2013
DOI: 10.4028/www.scientific.net/amr.778.840
|View full text |Cite
|
Sign up to set email alerts
|

Condition Assessment of the Timber Structures of a Century-Old Industrial Building Using a Nondestructive Inspection Procedure

Abstract: This paper reports an in situ inspection project conducted on heavy timber structures of a century-old industrial building at a paper manufacturing facility. A nondestructive inspection procedure was employed to evaluate the true condition of the heavy timbers that serve as the main framing structure of the building. The on-site investigation involved monitoring of the microclimate environment resulting from the paper machine operations, wood species identification, wood moisture content measurements, and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Then, the entire ancient building was preserved and maintained, and the wooden components with insufficient strength were replaced as well [41]. In 2013, Wang et al conducted an NDT of a century-old wood-frame building at a paper manufacturing facility in Wisconsin, USA [42]. Field investigations included monitoring microclimatic environmental changes caused by paper machine operations, identification of wood species, measurement of wood moisture content, and internal rot detection with a Resistograph and a stress wave transmission velocity method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the entire ancient building was preserved and maintained, and the wooden components with insufficient strength were replaced as well [41]. In 2013, Wang et al conducted an NDT of a century-old wood-frame building at a paper manufacturing facility in Wisconsin, USA [42]. Field investigations included monitoring microclimatic environmental changes caused by paper machine operations, identification of wood species, measurement of wood moisture content, and internal rot detection with a Resistograph and a stress wave transmission velocity method.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that many elements were in poor conditions, which appeared as extensive internal and external aging. In addition, some damaged wooden elements due to fire were identified as well as some completely defective parts [42]. In 2015, Ross et al conducted a nondestructive evaluation of a scenic tower (also known as Eagle Tower) located in Peninsula State Park, Wisconsin, USA [43].…”
Section: Introductionmentioning
confidence: 99%